Introduction to Criminal Justice - Senna, Joseph J. (Cengage Learning, Inc, 2008)
Want to get the most out of your introduction to criminal justice course and ace your exams? Let best-selling authors Larry J. Siegel and Joseph J. Senna show you the way in this Eleventh Edition of INTRODUCTION TO CRIMINAL JUSTICE, International Edition. Siegel and Senna take you on an exciting behind- the-scenes look at the workings of the police, courts, and correctional systems. Helping you understand even the most complex concepts and topics, this Eleventh Edition includes plenty of learning tools to guide your study. With a new "Careers in Criminal Justice" feature in every chapter, interactive online tools, and many real-world criminal justice examples throughout, you will discover the rewards and challenges that criminal justice professionals experience daily